Phospholipid remodeling in dopaminergic neurons: role of α-synuclein variants and iron overload - Sánchez Campos, Sofía (2013)
Increased levels of α-synuclein (α-syn) and iron-overload are pathognomonic signs of dopaminergic neurons in Parkinson’s disease (PD) patients. Moreover, iron and fatty acid (FA) availability are predisposing factors for pathological α-syn aggregation. In this work, we characterized the phospholipid remodeling pathways that regulate FA availability in dopaminergic neurons overexpressing α-syn variants (WT and A53T) and exposed to iron-overload. Increased cellular oxidant and lipid peroxidation levels were observed in dopaminergic neurons exposed to iron-overload. The inhibition of calcium-independent phospholipase A2 (deacylation pathway) provoked an increase in the extent of cellular damage induced by iron-overload. In this connection, phospholipid acylation was differentially affected by iron overload and the presence of α- syn variants. FA incorporation into phosphatidylcholine (PC) and phosphatidylethanolamine (PE) was increased in dopaminergic neurons harboring WT α-syn. This acylation profile was not altered by iron-overload. Neurons expressing A53T α-syn (a variant present in autosomic dominant PD and with high iron affinity) showed a diminished FA esterification in PC and PE. This effect was enhanced in iron overloaded neurons. Our results show that FA availability is differentially regulated by α-syn variants and iron overload in this in vitro model of PD